(3efXheI aj Yde GdcdGes - (3GdnZpqRj GdYGeQj GdbQTj GdOeTbqj, CHh GdecGQe, fLe GdOjf, eMeO Hf eMeO Hf eMeO, (B1061 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg bGd fLe GdOjf GdZRj (B: (3jGQHfG cajJfG KdGKI ajeG eVi ef GdReGf hZHQ (B- (3ecGf gdGcge HCeQ Gddg aj eG Ohf YGe heUhG deG GdMajs
(3BNQgG (B:s
(3CSQY eG jMQb fGQG CbQJ TjA EdjgdG YfOeG JdJgHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 63s
(3eYLe GdeDdajf (B3 / 685s
(3NdGUI GdCKQ (B4 / 189 - 200s
(3GdchGcH GdSGFQI (B( (3ebOeI GdfGTQ (B)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds